Abemaciclib, a third CDK 4/6 inhibitor for the treatment of hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced or metastatic breast cancer. Issue 1 (2nd January 2021) - El Hachem, Georges; Gombos, Andrea; Awada, Ahmad
ABSTRACT: Introduction: The field of metastatic luminal breast cancer (hormone receptor positive, HER-2 negative) is dynamic and evolving, harboring some of the most significant therapeutic advances in medical oncology. Over the last decade, many pivotal trials showed excellent results with drastic improvements in survival as well as the quality of life of metastatic luminal breast cancer patients. Areas covered: The successful inhibition of the cyclinD/cyclin-dependent kinases 4 and 6 (CDK4/6)–retinoblastoma protein (RB) pathway with potent CDK4/6 inhibitors improved the outcome of advanced luminal breast cancers. Abemaciclib is the third CDK 4/6 inhibitor arriving to the market after palbociclib and ribociclib. Here, we describe the biology of the CDK4/6 pathway and summarize clinical data of previously published pivotal trials emphasizing the efficacy and toxicity of abemaciclib. The aim was to define its place in the current guidelines and to make a brief comparison with other available drugs of same class in the absence of cross trials comparison. Expert opinion: As there are no available biomarkers to predict response or resistance to abemaciclib, the promising overall survival data of MONARCH-2 could possibly impact the clinician's choice to optimize treatment for endocrine-resistant metastatic breast cancer.